How Do Young Entrepreneurs Enhance Problem-Solving Skills and Quality Business Decision Making? Understanding the Driver Factors - Constantine, Winston; Thedy, Patricia Aprilia; Claudia, Jenica; Anggriawan, Claudia; Angdris, Jacqueline Fidelia; Ardyan, Elia (Jurnal Entrepreneur dan Entrepreneurship, 2024)
Colleges should be able to provide the ability to solve problems and make effective decisions. The aim of this study is to investigate the correlation between entrepreneurial creativity and entrepreneurial self-efficacy with problem-solving skills and the quality of business decision-making. The method of this study utilizes a quantitative research methodology, involving 195 students who are owners of firms and actively engaged in building such enterprises. Respondents must have experience in solving problems and making decisions that significantly impact their businesses. The data was analyzed using SEM-PLS. The results of this study indicate that entrepreneurial creativity can enhance entrepreneurial self-efficacy but does not improve problem-solving skills. Whereas, entrepreneurial self-efficacy can improve problem-solving skills. The improvement in problem-solving skills will have a positive impact on the quality of business decision-making.